Administration Guidelines According to The School Development Strategies of School in Educational Fund Project, Lop Buri Province - Phunpraphaphon, Supawee; Chucheep, Sunchai; Worapanya, Sermsap (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
The purposes of this research were to 1. study the administrative situation with the school development strategy in the Education Fund Project, Lopburi Province; 2. develop administration guidelines according to the school development strategies of schools in the Educational Fund Project, Lop Buri Province. The sample group includes 4 directors or acting director positions and 31 teachers, totaling 35 samples. The research instrument included a Rating Scale questionnaire 5-level and an in-depth interview. The data was analyzed by using percentages, mean values, and standard deviations, and content analysis was used using descriptive writing. The results showed that: 1. Administrative situation with the school development strategy in the Education Fund Project, Lopburi Province when considering the total, were at a high level, sorted by average from highest to lowest as follows: 1) Strategy 3 Development of students’ characteristics to have discipline, morality, and ethics, 2) Strategy 4 Development of life skills, 3) Strategy 5 Quality school management, 4) Strategy 1 Developing teachers to have potential in organizing teaching and learning activities, 5) Strategy 2 Raising learning achievement. 2. Develop administration guidelines with the school development strategy in the Lop Buri Provincial Education Fund Project consists of 2 strategies, namely Strategy 1 Developing teachers to have the potential to organize teaching and learning activities, which consists of 7 approaches, such as developing teachers’ potential to match students’ abilities and having the potential to classify individual student’s abilities; strategy 2, Elevating academic achievement consists of 11 approaches such as intellectual development of students based on curriculum guidelines and student-centered learning process.